Pengembangan Lembar Kerja Peserta Didik (LKPD) Bermuatan STEM pada Materi Energi Kelas IV Sekolah Dasar - Anita Anita; Siti Nur Asmah; Muhammad Aqmal Nurcahyo (Edu Berkah Khatulistiwa, 2023)
LKPD containing STEM methods is applied to grade IV elementary schools in delivering material about energy which involves many events that exist in the real world everyday. Students will be taught the technique of creating a simple tool related to energy matter, then apply various existing technologies in explaining energy matter. The description above attracts researchers to develop teaching materials about STEM-laden LKPD through R&D research. This research is a type of R&D (Research and Development) or development which is interpreted as a research conducted by creating a product and then testing its effectiveness. Based on the validation of material experts, design experts and linguists. The development of STEM-charged LKPD on energy materials at SDN 41 Sungai Raya can be categorized as feasible. This feasibility is obtained from expert validators, both linguists, design, and material experts. Overall, the feasibility aspect of the material obtained a score of 76% in the